American civil religion: the rise of a chosen people and its current crisis (Journal of the Sociology and Theory of Religion, 2018)
How is it possible to speak of an American civil religion? And how was your national identity generated? What does it mean to be American today and how do you relate to others? This book starts from the identity problem reactivated with globalization and its crises, reason why has returned to pay attention to the religious factor. As the author affirms, this problem is more complex and confused by postmodern veils (eg relativism, political correctness, weak thinking), and even more so in the United States of America (USA), thus hindering its urgent and necessary revision identity and solidarity to this day.